Physical Exercise for Individuals with Hypertension: It Is Time to Emphasize its Benefits on the Brain and Cognition - Rêgo, Maria LM (Clin Med Insights Cardiol, 2019)
Hypertension affects more than 40% of adults worldwide and is associated with stroke, myocardial infarction, heart failure, and other cardiovascular diseases. It has also been shown to cause severe functional and structural damage to the brain, leading to cognitive impairment and dementia. Furthermore, it is believed that these cognitive impairments affect the mental ability to maintain productivity at work, ultimately causing social and economic problems. Because hypertension is a chronic condition that requires clinical treatment, strategies with fewer side effects and less-invasive procedures are needed. Physical exercise (PE) has proven to be an efficient and complementary tool for hypertension management, and its peripheral benefits have been widely supported by related studies. However, few studies have specifically examined the potential positive effects of PE on the brain in hypertensive individuals. This narrative review discusses the pathophysiological mechanisms that hypertension promotes in the brain, and suggests PE as an important tool to prevent and reduce cognitive damage caused by hypertension. We also provide PE recommendations for hypertensive individuals, as well as suggestions for promoting PE as a method for increasing cognitive abilities in the brain, particularly for hypertensive individuals.